2010
DOI: 10.3858/emm.2010.42.3.018
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species enhance differentiation of human embryonic stem cells into mesendodermal lineage

Abstract: Recently, reactive oxygen species (ROS) have been studied as a regulator of differentiation into specific cell types in embryonic stem cells (ESCs). However, ROS role in human ESCs (hESCs) is unknown because mouse ESCs have been used mainly for most studies. Herein we suggest that ROS generation may play a critical role in differentiation of hESCs; ROS enhances differentiation of hESCs into bi-potent mesendodermal cell lineage via ROS-involved signaling pathways. In ROS-inducing conditions, expression of pluri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(103 citation statements)
references
References 22 publications
(41 reference statements)
8
93
0
Order By: Relevance
“…Hence, the observed higher resistance of undifferentiated hESC to oxidative stress and genotoxic stress compared to somatic cell types, as reported by our previous studies [5,6], could be due to lower innate basal intracellular levels of ROS within hESCs compared to somatic cell types. Our findings are consistent with previous studies which showed that ROS play crucial roles as secondary messengers during stem cell differentiation into various somatic lineages [10,11], so that an increase in ROS levels in differentiated stem cell progenies is therefore expected. Hirano and Tamae [12] and Kuboyama et al [13], also reported that undifferentiated embryonic stem cells were more resistant to DNA damage induced by the ROS -8-oxoguanine (which is known to generate GC-to-TA point mutations in genomic DNA), as compared to their differentiated progenies.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, the observed higher resistance of undifferentiated hESC to oxidative stress and genotoxic stress compared to somatic cell types, as reported by our previous studies [5,6], could be due to lower innate basal intracellular levels of ROS within hESCs compared to somatic cell types. Our findings are consistent with previous studies which showed that ROS play crucial roles as secondary messengers during stem cell differentiation into various somatic lineages [10,11], so that an increase in ROS levels in differentiated stem cell progenies is therefore expected. Hirano and Tamae [12] and Kuboyama et al [13], also reported that undifferentiated embryonic stem cells were more resistant to DNA damage induced by the ROS -8-oxoguanine (which is known to generate GC-to-TA point mutations in genomic DNA), as compared to their differentiated progenies.…”
Section: Discussionsupporting
confidence: 93%
“…A low-level ROS pulse is required specifically for cardio and vascular differentiation from mES cells [5]. ROS also enhances spontaneous differentiation of human ES cells into mesendodermal cell lineage [47].…”
Section: Discussionmentioning
confidence: 99%
“…Further the growth of hESCs in ROS-inducing conditions (BSO treatment, which inhibits intracellular glutathione and enriches ROS levels) has been shown to induce an up-regulation in mesodermal and endodermal differentiation and this occurred through MAPK signalling (Ji et al, 2010). These studies are the first to demonstrate ROS-mediated differentiation in hESCs.…”
Section: Mapk Pathway-mediated Hesc Differentiationmentioning
confidence: 79%
“…This study found a link between the eicosanoid signalling pathway and pluripotency and several oxidized metabolites and the promotion of neuronal and cardiac differentiation. A previously mentioned study found that an increase in ROS, which would lead to an increase in oxidized metabolites, led to cardiac differentiation (Serena et al, 2009) and mesodermal/ endodermal differentiation (Ji et al, 2010). Oxygen tension may also affect differentiation (Chen et al, 2010b;Lim et al, 2011) as, similar to hESC culture, differentiation protocols do no tend to use physiological levels of oxygen, as is shown in the production of retinal progenitor cells (Bae et al, 2011), mesoderm and cardiac cells (Niebruegge et al, 2009), chondrocytes (Koay andAthanasiou, 2008) and functional endothelium (Prado-Lopez et al, 2010) from hESCs.…”
Section: Metabolomicsmentioning
confidence: 93%